Analisis Kondisi Sosial Ekonomi Petani Berdasarkan Komoditas Pertanian di Kecamatan Wakorumba Selatan - Novriana Sartika; Weka Widayati; Noor Husna Khairisa; Irfan Ido (Universitas Halu Oleo, 2023)
ABSTRACT The South Wakorumba Subdistrict has two primary commodities, namely cashew and coconut. The cultivation of each commodity results in socioeconomic characteristics divergence among farmers. This research aims to: (1) Understand the distribution patterns of agricultural commodities in the region; (2) Ascertain the socioeconomic conditions of the community based on agricultural commodities. The data used in this study include the coordinates of garden locations and interviews with 83 farmers. The data was analyzed using quantitative descriptive analysis. The findings of this study are: (1) Coconut commodities are spread in the lowlands with a dryland farming pattern, while cashew commodities are dispersed in the highlands with a similar dryland farming pattern; (2) Socioeconomic conditions of coconut farmers are as follows: dominant age is 41-50 years, the majority have a high school education, most have less than 10 years of farming experience, the average household has 3-4 members, farmland size is predominantly 1-2 hectares, and income per harvest ranges from 2.000.000 – 3.000.000 IDR. The socioeconomic conditions for cashew farmers are: the dominant age is 51-60 years, most have a high school education, the general farming experience is 10-15 years, households have 3-4 members, dominant farmland size is 1-2 hectares, and income per harvest is 2,000,000 - 3.000.000 IDR.